Perancangan Sudu Turbin Angin Sumbu Vertikal Tipe Heliks Untuk Meningkatkan Kinerja Pada Kecepatan Angin Rendah - Yusril Mahendra; Legisnal Hakim; Sunaryo (Universitas Muhammadiyah Metro, 2024)
When constructing wind turbine blades, one of the challenges is deciding on the number of blades, which in turn requires determining their height and diameter. Wind turbine blades need to be structurally sound so that they can spin with minimal wind forces. The primary objectives of this study are to ascertain the wind turbine blade height, diameter, form (specifically, helical type), and number of blades. Literature review, shaft and blade design, analysis, and discussion are all components of the design technique that the research employs. The design findings showed a wind turbine with a 2,280 mm blade height, a 1,820 mm blade diameter, a 13 mm shaft diameter, and a 90° twist, all at a low wind speed of 4.3 m/s.